1975
DOI: 10.1017/s0003356100030427
|View full text |Cite
|
Sign up to set email alerts
|

The comparative performance of purebred and crossbred boars in commercial pig production

Abstract: An investigation was undertaken to evaluate the crossbred boar per se, and also to assess the value of including the American Hampshire into a first-cross sire. Groups of three boars were placed on each of 20 farms. Each group contained a purebred white (Landrace or Large White), a crossbred white and a crossbred Hampshire boar. Co-operators were asked to obtain at least six litters by each boar, record their performance to weaning, and provide a sample of the progeny of each boar to be reared under standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…These results agree with those of Schlote et al (1974), Lishman et al (1975 and Fahmy and Holtmann (1977a), who found litters produced by crossbred boars to be similar in size and weight to those produced by purebred boars.…”
Section: Crossbred Siressupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with those of Schlote et al (1974), Lishman et al (1975 and Fahmy and Holtmann (1977a), who found litters produced by crossbred boars to be similar in size and weight to those produced by purebred boars.…”
Section: Crossbred Siressupporting
confidence: 93%
“…Several researchers (e.g., Rempel et al, 1964;Lishman et al, 1975;Fahmy and Holtmann, 1977a) found little differences in variability, and, in some cases, progeny of crossbred boars were less variable.…”
Section: Crossbred Siresmentioning
confidence: 99%
“…Curran et al (1972) found that crossbred pigs from Pietrain x Hampshire boars compared favourably to crossbred pigs from Large White boars for growth, feed conversion, depth of backfat and killing-out percentage. Comparing purebred Landrace and Large Whites to two-way crosses between Landrace, Large Whites and Hampshires, Lishman et al (1975) found no differences for growth rate, feed conversion or depth of backfat between progeny of crossbred and purebred boars. Sellier (1973) found no significant differences between progeny of Blanc de l'Ouest x Pietrain and purebred Pietrain boars for daily gain, but Blanc de l'Ouest x Pietrain-sired pigs were superior for age at slaughter.…”
Section: Discussionmentioning
confidence: 81%
“…Although several different types of crossbred boars have been examined previously for the market performance of their offspring (Rempel, Comstock and Enfield, 1964;Curran, Lean, Duckworth and Holmes, 1972;Sellier, 1973;King and Thorpe, 1974;Lishman, Smith, Bichard and Thompson, 1975;Fahmy and Holtmann, 1977), the Hampshire xDuroc has not been investigated. This study compares Hampshire x Duroc boars with purebred Hampshire, Duroc and Landrace boars for growth and market perfor mance of their progeny MATERIAL AND METHODS Fourteen boars-three Hampshire x Duroc, three Hampshire, three Duroc and five Landrace-were selected only on the basis of general condition, conformation and strength of feet and legs, but were not selected for production characteristics such as rate of gain and depth of backfat.…”
mentioning
confidence: 99%
“…The advantage of a crossbred female is clear, but there has been less research concerning the use of crossbred boars. Studies on young crossbred boars have generally shown an advantage in testis weight, mating behavior and conception rate (Hauser et al, 1952;Lishman et al, 1975;Wilson et al, 1977;Conlon and Kennedy, 1978;Neely et al, 1980), but more information is needed. There is also less information on the performance of the Landrace and Spotted breeds than for Durocs, Yorkshires or Hampshires.…”
Section: Introductionmentioning
confidence: 99%